Identification of Branched-Chain Fatty Acid Producing Phenotypes in Holstein Cows. (7th June 2021) - Picklo, Matthew; Kalscheur, Kenneth; Bukowski, Michael; Harnly, James; Fukagawa, Naomi
Abstract: Objectives: Branched chain fatty acids (BCFA) are rumen-derived fatty acids comprising about 2% of bovine milk fatty acids. BCFA possess anti-inflammatory properties and enriching the BCFA content of bovine milk may provide human health benefits of milk consumption. In this work, we determined whether high vs low forage diets impact the BCFA content of milk from Holstein cows and identified fatty acid phenotypes in high vs low BCFA-containing milks. Methods: In this study, 62 Holstein cows were fed for 70 days, in a cross-over design fashion, either a high forage: concentrate (HF: C) diet or a low forage: concentrate (LF: C) diet. At the end of the 70-day feeding period, cows were switched to the alternate feeding arm. Milk samples were collected prior to the start of the first feeding period and at the end of each treatment period. Milk fatty acid content was determined by fatty acid methyl ester analysis. Paired t-tests, one-way ANOVA, and sparse partial least squares discriminant analysis (sPLSDA) were used to analyze the data. Results: The total milk fatty acid concentration at the end of HF: C diet period was greater than that of the LF: C diet (4.2 ± 0.9 g/100 mL vs 3.95 ± 0.9 g/100 mL). sPLSDA demonstrated clear separation of the dietary treatments, with BCFA and odd-chain fatty acids as primary determinants. Total BCFA content was elevated by HF: C intake (1.86 ± 0.13%) vs LF: C intake (1.77 ± 0.14%). Quintile separation of high vs low BCFA milks resulted in 4 groups (n = 12) HF: C/low BCFA, HF: C/high BCFA; LF: C/low BCFA, and LF: C/high BCFA. The total BCFA contents of the low BCFA milks were not different regardless of forage content (1.70 ± 0.06% and 1.61 ± 0.04%) and were lower than the high BFCA milks (2.04 ± 0.11% and 1.98 ± 0.11%). Milks from the high BCFA quintiles had lower saturated fatty acid (SFA) content but higher oleic acid content than milks from the low BCFA quintiles. Of the 62 cows, 5 cows were identified as high BCFA producers and 6 cows as low BCFA producers regardless of the LF: C or HF: C diets. Conclusions: The data demonstrate that the BCFA content of milk is diet-sensitive but variation in cow responses suggest factors such as genotype or rumen microbiome composition may play significant roles. The potential to produce milk with high BCFA content and lower SFA content needs further study. Funding Sources: USDA-ARS Projects 3062–53000-001–00D, 5090–31000-025–00D, 80–8040-05–01-0000–0000.